2021
DOI: 10.1096/fj.202100198rr
|View full text |Cite
|
Sign up to set email alerts
|

Paternal high protein diet modulates body composition, insulin sensitivity, epigenetics, and gut microbiota intergenerationally in rats

Abstract: Mounting evidence demonstrates that paternal diet programs offspring metabolism. However, the contribution of a pre‐conception paternal high protein (HP) diet to offspring metabolism, gut microbiota, and epigenetic changes remains unclear. Here we show that paternal HP intake in Sprague Dawley rats programs protective metabolic outcomes in offspring. Compared to paternal high fat/sucrose (HF/S), HP diet improved body composition and insulin sensitivity and improved circulating satiety hormones and cecal short‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…However, the controversial role of mucin in different diseases might determine the diverse effect of Akkermansia (Cabrera-Rubio et al, 2019;Xie and Fei, 2021). For example, Akkermansia muciniphila was recommended as the promising probiotic against metabolic disorders (Zhang et al, 2019), while the studies in a high-fructose (Wang et al, 2020) or high-fat diet showed the increase of Akkermansia (Xie and Fei, 2021), and Akkermansia could reduce the important enzymes which prevented hyperglycemia and hyperlipidemia (Chleilat et al, 2021). Besides, the enrichment of Akkermansia has been reported in inflammatory states such as alcohol-induced steatohepatitis (Ran et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, the controversial role of mucin in different diseases might determine the diverse effect of Akkermansia (Cabrera-Rubio et al, 2019;Xie and Fei, 2021). For example, Akkermansia muciniphila was recommended as the promising probiotic against metabolic disorders (Zhang et al, 2019), while the studies in a high-fructose (Wang et al, 2020) or high-fat diet showed the increase of Akkermansia (Xie and Fei, 2021), and Akkermansia could reduce the important enzymes which prevented hyperglycemia and hyperlipidemia (Chleilat et al, 2021). Besides, the enrichment of Akkermansia has been reported in inflammatory states such as alcohol-induced steatohepatitis (Ran et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Ethical approval was granted by the University of Calgary Animal Care Committee (Protocol#AC15-0079) and conformed to the Guide to the Care and Use of Experimental Animals. Obesity was induced in 8-week-old female Sprague-Dawley rats using a 10-week feeding period with a high fat/high sucrose diet (HFS, 39% fat and 44% sucrose, Dyets #102412), the composition of which has been previously published (17). Given that Sprague-Dawley rats can be obesity-prone or obesity-resistant when fed a HFS diet (18), we chose the top n = 45 best weight gainers from the n = 135 rats included in the diet-induced obesity protocol (Figure 1).…”
Section: Animals and Samplesmentioning
confidence: 99%
“…While the effects of HFD on individuals have been intensely studied over the past 30 years, the potential transgenerational impacts of HFD—more specifically, the impacts of paternal diet on obesogenic phenotypes in the offspring—are not well understood. Paternal HFD, leading to diet-induced obesity (DIO) in rats 3 5 , results in offspring with delayed growth, impaired liver function 6 10 , and deviations in social and anxiety-like defensive behavioral responses 11 , epigenetic reprogramming 12 , 13 , and alterations to the gut microbiome 14 , 15 . Recently, paternal diet has been implicated in the development of inter- and transgenerational offspring phenotypes 16 18 .…”
Section: Introductionmentioning
confidence: 99%